BOARD CHARACTERISTICS AND CAPITAL STRUCTURE: A CASE STUDY OF SELECTED HOTELS & RESTAURANTS IN SRI LANKA - Priya, K.; Nimalathasan, B. (My University, 2013)
The board characteristics are generally seen as the major corporate control mechanism in Sri Lanka. Board characteristics and capital structure are correlated but a casual effect has not been established yet. The goal of this paper is to study this issue by identifying a specific channel through board characteristics affect capital structure. This study examines the relationship between board characteristics and capital structure among selected hotels and restaurants in Sri Lanka. Which covered over a period of past 5 years from 2008 to 2012, Correlation and regression analysis statistics were used in the analysis and findings suggest that there is a significant relationship exists between board characteristics and capital structure among the hotels and restaurants in Sri Lanka. However, the findings of this paper are based on a study conducted on the selected hotels and restaurants. Therefore, the results are valid for this sector. The results add insight on the relation between monitoring mechanisms and capital structure of hotels in an emerging market.
Keywords: Board characteristics; Capital structure; corporate governance; Hotels & Restaurants.